Designing a Records Management System for Amil Zakat Institutions using an Assignment Approach - Permatasari, Hanifah; Srirahayu, Agustina (Universitas Bina Darma, 2024)
In the digital era, effective archive management and performance reporting are essential for organizations, especially Lembaga Amil Zakat (LAZ) which has a great responsibility towards accountability and transparency. This research aims to design a Management Information System (SIM) to manage archives and performance reports with the assignment method, tailored to the needs of management in LAZ so that data management is more efficient and integrated. The method used is Rapid Application Development (RAD) which consists of three stages: Requirements Planning, Design, and Implementation. This research resulted in a SIM design with access divided into three levels of management, namely top level management, lower level management, and technical level management. Top level management plays a role in assigning tasks as well as monitoring the progress of tasks, middle level management assigns and monitors tasks as well as receiving and editing tasks, while technical level management only plays a role in collecting tasks. Centralized task collection will make it easier for LAZ to manage and search for important documents, archives, and reports. LAZ can use this design in answering the challenge of managing document data in the form of archives and performance reports that support zakat accountability, as well as contributing to the development of SIM for non-profit organizations.